Gold(I) vinylidene complexes as reactive intermediates and their tendency to π-backbond - Nunes dos Santos Comprido, Laura; Klein, Johannes E. M. N.; Knizia, Gerald; Kästner, Johannes; Hashmi, A. Stephen K. (Chemistry - a European journal, 2016)
We herein report a computational study of the bonding in gold(I) vinylidene complexes and compare them to their carbene and CO analogues. The relevance of these intermediates is analysed for the intramolecular cyclisation leading to vinyl sulfonates.